Systematics of the New Zealand Weevil Etheophanus Broun (Curculionidae: Molytinae) - Davis, Steven R.; Brav-Cubitt, Talia; Buckley, Thomas R.; Leschen, Richard A. B. (Zootaxa, 2019)
Etheophanus Broun is considered a molytine based on the form of the pharyngeal plate, presence of a small spiculum relictum in the male, and presence of a pair of small internal apodemes on the antero-lateral corners of the 5th abdominal ventrite of the female. Examination of primary type specimens and newer material confirm one new species Etheophanus kuscheli sp. n. and two synonomies (Etheophanus nitidellus Broun, 1923 [= Etheophanus obscurus Broun, 1923] and Etheophanus striatus Broun, 1910 [=Etheophanus punctiventris Broun, 1914]). Generic and species diagnoses, a key to the species, and lectotype designations for three species are included. Phylogenetic reconstructions based on a combined analysis of the nuclear 28S rRNA and mitochondrial cytochrome c oxidase subunit I genes confirmed the status of E. kuscheli and a species complex, the E. nitidellus/E. optandus clade distributed in the southern portion of the South Island. The relationship E. pinguis [northern North Island] (E. striatus [southern North Island, northern South Island] (E. kuscheli [northwestern South Island] (E. nitidellus, E. optandus [southwestern North Island]) corresponds to geographic patterns found in other beetle lineages. Etheophanus striatus is composed of three lineages, one widespread in the north and south islands and two allopatric populations in the northwest South Island. The E. nitidellus/E. optandus complex includes four distinct lineages, one restricted to Fiordland, the other three sympatric in the region affected by the Haast Corridor.